Design of Student Apartment Housing in Medan City, North Sumatra with A Green Architecture Theme - Fanny Fadillah; Melly Andriana; Dara Wisdianti (International Journal of Mechanical, Electrical and Civil Engineering, 2025)
The increasing number of students in major cities such as Medan has created an urgent need for temporary housing that is adequate, comfortable, and sustainable. In response, the Indonesian government, through the Ministry of Public Works and Public Housing (PUPR), launched the "One Thousand Towers Program," which includes the development of rental apartment buildings (Rusunawa) for students. However, housing provision must go beyond quantity—it must also consider environmental aspects and the quality of life for its occupants. Therefore, a green architecture approach serves as the foundation for the design of environmentally friendly student housing. This project aims to create a vertical residential facility that not only fulfills the basic function of shelter but also supports learning activities, social interaction, energy efficiency, and environmental sustainability. The design applies key principles of green architecture such as natural lighting, cross ventilation, the use of eco-friendly materials, and the integration of green open spaces. In addition to double-room residential units, the building is equipped with supporting facilities such as study areas, a library, cafeteria, and rooftop garden. The design methodology integrates both primary and secondary data analysis, as well as a comprehensive site study covering climate, noise levels, circulation, and building orientation. The building form concept is developed modularly and efficiently through mass transformation, resulting in an inner court that provides natural light and air. Supported by energy-saving utilities, this design is expected to offer a student housing solution that is not only functional and aesthetic but also contributes to sustainable and high-quality urban development.